Peningkatan Keterampilan Petani Melalui Pelatihan & Implementasi Komposter Pintar pada Kelompok Tani Desa Nangbelawan - Khairul, Khairul; Jantianus; Naibaho, Dameria; Karo Karo, Sastra (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2024)
The primary needs of farmers include fertilizers, both organic and chemical fertilizers; the gap between availability and needs and fertilizer subsidies have not been able to increase agricultural production. Fertilizer problems also occur in Karo Regency in general. PT Pupuk Indonesia (Persero) is asked to take firm action against distributors and official kiosks in Karo Regency that are proven to have committed violations or irregularities related to the distribution of subsidized fertilizers. These violations include selling above the highest retail price (HET), selling to farmers outside the electronic definitive group needs plan (e-RDKK), and selling in packages. Fertilizer availability also remains a significant problem for their farmer groups. Farmers in Nangbelawan Village sometimes innovate by making organic fertilizers from crop residues or household food consumption to overcome the scarcity of chemical fertilizers. However, the quality of this organic fertilizer cannot guarantee the quality of the crops grown by farmers. Based on the results of discussions and interviews, it was finally obtained that the Nangbelawan Village farmer group needed training on making quality organic fertilizer or compost. There is also the need for tools that can help make compost or organic fertilizer. Currently, many composter tools are sold freely, but due to limited knowledge and funds, the Nangbelawan Village Farmers Group has not been touched by this composter tool. The results of the service activities show that the Smart Composter utilizing Debok banana (banana stem) waste, cow dung, water hyacinth, and rice straw has been successfully designed. It is expected to produce compost fertilizer effectively, and this composter is very suitable for use in Nangbelawan village, where the location of the area is an agricultural and livestock area. Hence, it is rich in raw materials.